2015
DOI: 10.1016/j.ajo.2015.09.017
|View full text |Cite
|
Sign up to set email alerts
|

Factors Predicting Visual Acuity Outcome in Intermediate, Posterior, and Panuveitis: The Multicenter Uveitis Steroid Treatment (MUST) Trial

Abstract: Purpose To identify factors associated with best-corrected visual acuity (BCVA) presentation and two-year outcome in 479 intermediate, posterior, and panuveitic eyes. Design Cohort study using randomized controlled trial data Methods Multicenter Uveitis Steroid Treatment (MUST) Trial masked BCVA measurements at baseline and 2 years’ follow-up used gold standard methods. Twenty-three clinical centers documented characteristics per protocol, which were evaluated as potential predictive factors for baseline B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 29 publications
(45 reference statements)
0
17
1
Order By: Relevance
“…This was recently reported in the Multicenter Uveitis Steroid Treatment trial. In this study, the authors speculated that, in intermediate, posterior and panuveitic eyes, successful control of inflammation tended to be associated with visual improvement; in contrast, the persistence or incidence of vitreous haze was associated with a worsening condition 19. In contrast to Lobo et al ,11 we did not identify additional factors associated with outcome, such as older age, African ethnicity or multifocal choroiditis.…”
Section: Discussioncontrasting
confidence: 69%
“…This was recently reported in the Multicenter Uveitis Steroid Treatment trial. In this study, the authors speculated that, in intermediate, posterior and panuveitic eyes, successful control of inflammation tended to be associated with visual improvement; in contrast, the persistence or incidence of vitreous haze was associated with a worsening condition 19. In contrast to Lobo et al ,11 we did not identify additional factors associated with outcome, such as older age, African ethnicity or multifocal choroiditis.…”
Section: Discussioncontrasting
confidence: 69%
“…30,31 The health-care burden is significant, where noninfectious uveitis accounts for substantial medical, social, and workload costs in the United Stated of America and aligns with data that persistent disease gives rise to considerable ocular and systemic morbidity. 24,[32][33][34] The clinical phenotype of non-infectious intraocular inflammation is replicated in experimental animal models that are driven by immune responses to self-antigen. 35 The animal models, such as experimental autoimmune uveoretinitis (EAU), support a role for autoimmunity with clinical-pathological features bearing remarkable similarity to man.…”
Section: Understanding Uveitismentioning
confidence: 99%
“…For example, the Multicenter Uveitis Steroid Trial found that patients with IU had a relatively good prognosis, except when macular thickening and edema were detected on optical coherence tomography (OCT) scans combined with active inflammation ( figure 3C ). 28 Moreover, a retrospective case review at a tertiary center found that 22.5% of patients with IU did not require treatment, and 60% had relatively preserved visual acuity after 10 years of follow-up. 29 Hence, the aim of management is to treat sight-threatening features (not uncomplicated or asymptomatic IU) such as glaucoma, cataract, epiretinal membrane, optic disc edema, retinal vasculitis, and retinal detachment.…”
Section: Shared Clinical Features Of Ms and Iumentioning
confidence: 99%